Stretchable hybrid bilayered luminescent composite based on the combination of strain-induced and triboelectrification-induced electroluminescence - Chen, Yanghui; Wei, Xiaoyan; Li, Huayang; Fan, Youjun; Hu, Weiguo; Zhu, Guang (American Chemical Society, 2019)
High luminescence intensity from materials that are excited by external stimuli is highly desired. In this work, a stretchable hybrid luminescent composite (HLC) that has multiple luminescence modes is reported. The luminescence can be excited either by externally applied mechanical strain or by a moving object that slides against the HLC. When the HLC is deformed, such as being twisted or folded, the ZnS/Cu phosphor experiences mechanical strain that trigger the mechanoluminescence (ML) of the phosphors. Moreover, as the HLC slides against a contact object, the triboelectrification at the contact interface induces the electroluminescence of phosphor. Here, a series of internal and external factors were studied on how they influence the luminescent intensity. It is found that the luminescent intensity from the two modes can be superposed. The HLC material was used to fabricate a fiber-based luminescent device that can be driven by air flow. The overall luminescent intensity is enhanced by over 72% compared to that obtained solely from the ML. The HLC reported in this work has such potential applications as self-powered light sources and sensors as means of detecting dynamic motions and interaction